Proportion of Patients Pulmonary Cancer With History of Slow Diagnosis Due to Diagnosis as Lung Tuberculosis - Cut Yulia Indah Sari; Faisal Yunus; Elisna Sjahruddin (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2019)
Background: In tuberculosis (TB) endemic countries, the diagnosis delay in lung cancer is due to initially misdiagnosed as pulmonary tuberculosis. The major concern that rose since early diagnosis of lung cancer could improve survival by tumor resectability chance and chemo-radiotherapy modality options. This study objective was to find out the proportion of lung cancer diagnosis delay due initially to misdiagnosed as pulmonary TB. Method: The cross-sectional study was held in Persahabatan Hospital and the subjects were histopatologically proven lung cancer patients between September 2012 to February 2013 involving totally 100 patients. The diagnosis delay were determined as whether the patients had been diagnosed as pulmonary tuberculosis and received anti-tuberculosis treatment (ATT) more than one month since current symptoms onset. All patients were interviewed and all chest X-rays were documented. Results: Fourty one of 100 patients were diagnosed as pulmonary TB and 29 of 41 patients received ATT more than one month. It consisted of 21 men and 8 women with the mean age of 51.5 years old. The cytology and histopatological biopsy revealed 28 Non Small Cell Lung Cancer (NSCLC) cases, and One Small Cell Lung Cancer (SCLC) case with all case were in end stage condition (6 cases in stage III and 22 cases in stage IV). Pre-referral sputum Acid Fast Bacilli (AFB) was conducted in only 9 cases with all negative results. Mean duration of ATT taken was 4.5±0.4 months. The ATT were given by 13 general practitioners, 12 pulmonologists and 4 internists. Discussion: Similar radiological findings in highly incidence of pulmonary TB could cause a large number of diagnosis delay in lung cancer due to initially diagnosed as pulmonary tuberculosis. Without proper investigation based on International Standard of TB Care, starting ATT with inadequate evaluation leads to diagnosis delay and lung cancer progression. (J Respir Indo 2019; 39(2): 92-102)